On the Possibility of Democracy and Rational Collective Choice - Claude Hillinger (Ludwig-Maximilians-Universität München, Volkswirtschaftliche Fakultät, 2004)
The paper challenges the 'orthodox doctrine' of collective choice theory according to which Arrow's 'general possibility theorem' precludes rational decision procedures generally and implies that in particular all voting procedures must be flawed. I point out that all voting procedures are cardinal and that Arrow's result, based on preference orderings cannot apply to them. All voting procedures that have been proposed, with the exception of approval voting, involve restrictions on voters expressions of their preferences. These restrictions, not any general impossibility, are the cause of various well known pathologies. In the class of unrestricted voting procedures I favor 'evaluative voting' under which a voter can vote for or against any alternative, or abstain. I give a historical/conceptual analysis of the origins of theorists' aversion to cardinal analysis in collective choice and voting theories.
urn:nbn:de:bvb:19-epub-429-9
Keywords: D71; D72; 330; Arrow's paradox; approval voting; cardinal collective choice; instant runoff voting; voting paradoxes